Plasma pharmacokinetics of ceftolozane/tazobactam in pediatric patients with cystic fibrosis. Issue 8 (18th May 2020) - Arrieta, Antonio C.; Ang, Jocelyn Y.; Zhang, Zufei; Larson, Kajal B.; Yu, Brian; Johnson, Matthew G.; Rhee, Elizabeth G.; Feng, Ed H.; Rizk, Matthew L.
Abstract: Background: The antipseudomonal cephalosporin/β‐lactamase inhibitor combination ceftolozane/tazobactam could be a potential treatment option for cystic fibrosis (CF) pulmonary exacerbations. The pharmacokinetics (PK) of ceftolozane/tazobactam in children with CF merits further evaluation. Methods: This is a retrospective subgroup analysis of a phase 1, noncomparative trial that characterized PK, safety, and tolerability of single intravenous doses of ceftolozane/tazobactam in pediatric patients. This analysis compares ceftolozane and tazobactam plasma PK parameters, estimated from a population PK model, between patients with and without CF enrolled in that trial. Individual attainment of PK/pharmacodynamic (PD) targets of ceftolozane and tazobactam (free ceftolozane concentration >4 µg/mL for >30% and free tazobactam concentration >1 µg/mL for 20% of the dosing interval) in patients with and without CF were evaluated. Results: The study enrolled 18 patients aged greater than or equal to 2 to less than 18 years old, which included 9 with CF. Weight‐normalized ceftolozane PK parameters were similar between patients with CF (clearance: 0.16 L/h/kg, half‐life: 1.54 hours, volume of distribution: 0.26 L/kg) and without CF (clearance: 0.15 L/h/kg, half‐life: 1.62 hours, volume of distribution: 0.26 L/kg), as were most weight‐normalized tazobactam PK parameters. Weight‐normalized tazobactam clearance was higher in patients with CF (0.73 L/h/kg) than patients without CF (0.42 L/h/kg). All patients achieved the prespecified PK/PD targets for ceftolozane and tazobactam. Conclusions: This retrospective analysis demonstrated generally similar weight‐normalized plasma PK parameters for ceftolozane and tazobactam among children with and without CF; thus, projected doses for treatment of pediatric hospital‐acquired/ventilator‐associated pneumonia, which are higher than the pediatric complicated urinary tract infection/intra‐abdominal infection doses, may be appropriate for treatment of CF pulmonary exacerbation.